Development and Validation of RP-HPLC Method for the Simultaneous Estimation of Cedazuridine and Decitabine by in Bulk and its Pharmaceutical Dosage Form (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: A new sensitive accurate and precise reverse-phase high-performance liquid chromatography(RP-HPLC) method was developed for the simultaneous estimation of cedazuridine and decitabine in bulk andpharmaceutical formulation. Materials and Methods: Chromatographic separation was achieved through AltimaC18 column (4.6*150 nm, 5 μm) using 0.01 Kh2PO4:acetonitrile (60:40 v/v) mixture used as the mobile phase.The Waters 2695, Reciprocating Water-510 pump system with PDA detector, and EMPOWERPRO softwarewere monitored at detection wavelength 257 nm on flow rate 1 mL/min and the method was validated as perICH guidelines (ICH,Q2 [R1]). Results and Discussion: Cedazuridine and decitabine were eluted at 2.248 minand 2.956 min, respectively, with good resolution. Plate count and tailing factor were very satisfactory, so thismethod was optimized and to be validated. Conclusion: This RP-HPLC method was successfully applied for thesimultaneous determination of cedazuridine and decitabine in their pharmaceutical formulation and, hence, can beused for the routine analysis of these drugs in combined dosage form.